Cerebral blood flow variability in fibromyalgia syndrome: relationships with emotional, clinical and functional variables - Montoro, Casandra I.; Schüpbach, Daniel (PLOS ONE, 2018)
Objective This study analyzed variability in cerebral blood flow velocity (CBFV) and its association with emotional, clinical and functional variables and medication use in fibromyalgia syndrome (FMS). Methods Using transcranial Doppler sonography, CBFV were bilaterally recorded in the anterior (ACA) and middle (MCA) cerebral arteries of 44 FMS patients and 31 healthy individuals during a 5-min resting period. Participants also completed questionnaires assessing pain, fatigue, insomnia, anxiety, depression and health-related quality of life (HRQoL). Results Fast Fourier transformation revealed a spectral profile with four components: (1) a first very low frequency (VLF) component with the highest amplitude at 0.0024 Hz; (2) a second VLF component around 0.01-to-0.025 Hz; (3) a low frequency (LF) component from 0.075-to-0.11 Hz; and (4) a high frequency (HF) component with the lowest amplitude from 0.25-to-0.35 Hz. Compared to controls, FMS patients exhibited lower LF and HF CBFV variability in the MCAs (p < .005) and right ACA (p = .03), but higher variability at the first right MCA (p = .04) and left ACA (p = .005) VLF components. Emotional, clinical and functional variables were inversely related to LF and HF CBFV variability (r≥-.24, p≤.05). However, associations for the first VLF component were positive (r≥.28, p≤.05). While patients´ medication use was associated with lower CBFV variability, comorbid depression and anxiety disorders were unrelated to variability. Conclusions Lower CBFV variability in the LF and HF ranges were observed in FMS, suggesting impaired coordination of cerebral regulatory systems. CBFV variability was differentially associated with clinical variables as a function of time-scale, with short-term variability being related to better clinical outcomes. CBFV variability analysis may be a promising tool to characterize FMS pathology and it impact on facets of HRQoL.
Gesehen am 16.04.2020